VIDEO PLENARY 3: VID-THER-02: Endoscopic ultrasound-guided pancreatic duct drainage in a chronic pancreatitis with gastric outlet obstruction - Lakhtakia, Sundeep (Endosc Ultrasound, 2017)
A 40-year-old man, previously diagnosed alcoholic chronic pancreatitis, presented with abdominal pain and recurrent vomiting with significant weight loss for 1 month. Imaging confirmed dilated pancreatic duct with small pseudocyst in the pancreatic head. Endoscopic retrograde cholangiopancreatography (ERCP) was not feasible due to pyloroduodenal narrowing causing gastric outlet obstruction. Endoscopic ultrasound (EUS) confirmed small pseudocyst in the pancreatic head with dilated pancreatic duct. EUS-guided trans-gastric pancreatic duct drainage was done, and a 7 Fr single pigtail stent was placed, with the distal end across the papilla and proximal half in the stomach. His symptoms gradually improved with relief in pain and vomiting, associated with weight gain. Imaging confirmed resolution of pseudocyst. Repeat ERCP, 2 months later, confirmed significant reduction of the pyloroduodenal narrowing. A transpapillary pancreatic duct stent was placed after removal of previously placed EUS-guided pancreatic duct stent.